Placement of the fishing nets in deep waters - Mumbai Archive Project Team (Jio Institute, 2024)
Given the availability of fish-rich waters, a pleasant climate, and the economic opportunities that come with living by the coast, it is likely that the Kolis migrated to the Mumbai coastline gradually over many generations. Though they face considerable challenges in earning their livelihood, the Kolis have persevered with their traditional way of life on the sea.